2009
DOI: 10.1080/14767050802452309
|View full text |Cite
|
Sign up to set email alerts
|

Side effects of oral misoprostol for the prevention of postpartum hemorrhage: Results of a community-based randomised controlled trial in rural India

Abstract: Misoprostol is associated with a significant increase in postpartum maternal shivering and fever with no side effects for the newborn. Given its proven efficacy for the prevention of PPH, the benefits of misoprostol are greater than the associated risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 15 publications
3
28
0
3
Order By: Relevance
“…Récemment, certains auteurs ont montré l'efficacité du misoprostol, analogue de la prostaglandine E1, dans la prévention de l'hémorragie de la délivrance [2,3]. Il existe actuellement une littérature abondante sur l'apport du misoprostol dans la prévention de l'hémorragie de la délivrance en cas d'accouchement par voie basse [6,[8][9][10][11]. Il ressort clairement de l'analyse de ces travaux que l'ocytocine est sans conteste plus efficace que le misoprostol dans la prévention de l'hémorragie de la délivrance.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Récemment, certains auteurs ont montré l'efficacité du misoprostol, analogue de la prostaglandine E1, dans la prévention de l'hémorragie de la délivrance [2,3]. Il existe actuellement une littérature abondante sur l'apport du misoprostol dans la prévention de l'hémorragie de la délivrance en cas d'accouchement par voie basse [6,[8][9][10][11]. Il ressort clairement de l'analyse de ces travaux que l'ocytocine est sans conteste plus efficace que le misoprostol dans la prévention de l'hémorragie de la délivrance.…”
Section: Discussionunclassified
“…Il ressort clairement de l'analyse de ces travaux que l'ocytocine est sans conteste plus efficace que le misoprostol dans la prévention de l'hémorragie de la délivrance. Cette dernière molécule demeure, en revanche, plus efficace qu'un placebo dans la prévention de l'hémorragie de la délivrance et donc son utilisation pourrait être réservée aux situations d'absence de disponibilité de l'ocytocine et notamment dans les accouchements non médicalement assistés en cas de difficulté d'accès aux centres de santé et structures hospitalières comme dans les pays en voie de développement [6,8,9]. Les posologies de 600 mcg et 400 mcg per os utilisées à cet effet paraissent équivalentes en attendant les résultats d'essais prospectifs comparant ces deux doses [6].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…One trial comparing 600 micrograms oral versus 600 micrograms rectal misoprostol confirmed that the oral dose resulted in significantly higher rates of shivering (76 versus 54%) and fever (9 versus 1%) 7. Nevertheless, the reported rates of shivering and fever vary greatly in the literature 10. For example, rates of shivering and fever following a prophylactic oral dose of 600 micrograms of misoprostol range from 18 to 71% and from 1 to 38%, respectively 7,11,12.…”
Section: Introductionmentioning
confidence: 99%
“…After exclusion criteria were applied, seven studies remained (Figure 1), of which two were duplicate. Derman 13 and Patted 17 reported the results of their study in two separate papers: the former reporting effectiveness of misoprostol and the Programme 7. The EU is not responsible for views advanced here latter reporting side-effects experienced.…”
Section: Results Of Literature Searchmentioning
confidence: 99%